Nickel‐ or Cobalt‐Catalyzed Cross‐Coupling of Arylsulfonic Acid Salts with Grignard Reagents. Issue 10 (10th June 2015) - Malapit, Christian A.; Visco, Michael D.; Reeves, Jonathan T.; Busacca, Carl A.; Howell, Amy R.; Senanayake, Chris H.
Abstract The use of arylsulfonic acid salts as electrophiles in a nickel‐ or cobalt‐catalyzed cross‐coupling with Grignard reagents is described. Bis(tricyclohexylphosphine)nickel dichloride [NiCl2(PCy3)2] was found to be the optimal catalyst, and reactions with this catalyst proceeded in most cases at room temperature. The analogous cobalt catalyst [CoCl2(PCy3)2] was also found to promote the cross‐coupling reaction at higher temperature (60 °C).